2007
DOI: 10.2471/blt.06.033167
|View full text |Cite
|
Sign up to set email alerts
|

Can Malawi's poor afford free tuberculosis sevices? Patient and household costs associated with a tuberculosis diagnosis in Lilongwe

Abstract: Objective To assess the relative costs of accessing a TB diagnosis for the poor and for women in urban Lilongwe, Malawi, a setting where public health services are accessible within 6 kilometres and provided free of charge. Methods Patient and household direct and opportunity costs were assessed from a survey of 179 TB patients, systematically sampled from all public and mission health facilities in Lilongwe. Poverty status was determined from the 1998 Malawi Integrated Household Survey (MIHS). Findings On ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
109
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(123 citation statements)
references
References 9 publications
12
109
1
1
Order By: Relevance
“…In the study by Kemp et al [31] the poor faced direct and indirect costs of US$15 compared to US$48 faced by the non-poor in accessing a TB diagnosis; however, the poor spent 244 % of their total monthly income on TB diagnosis compared with 129 % for the non-poor. Relative to total income, therefore, the poor were twice as much affected as the non-poor, which makes the need to identify strategies for diagnosing TB that are cost-effective for the poor and their households evident [31].…”
Section: Direct Costs and Indirect Costsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study by Kemp et al [31] the poor faced direct and indirect costs of US$15 compared to US$48 faced by the non-poor in accessing a TB diagnosis; however, the poor spent 244 % of their total monthly income on TB diagnosis compared with 129 % for the non-poor. Relative to total income, therefore, the poor were twice as much affected as the non-poor, which makes the need to identify strategies for diagnosing TB that are cost-effective for the poor and their households evident [31].…”
Section: Direct Costs and Indirect Costsmentioning
confidence: 99%
“…In the study by Kemp et al [31] it was found that the poor in Lilongwe spend 57.5 % of their income on food, whereas the non-poor spend only 29.8 %. This meant that seeking a TB diagnosis cost the poor 574 % of their available non-food monthly income compared to 184 % for the non-poor [31].…”
Section: Direct Costs and Indirect Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…En el presente estudio, estos gastos representaron menos del 30% de los ingresos mensuales. Otro estudio realizado en Malawi por Kemp y col. sugiere que entre los costos de bolsillo que deben asumir el paciente y su familia, y el dinero que deja de recibir el enfermo por sus días de incapacidad, superan la media de ingresos de la población (17) . Es posible que el comportamiento que puede tener la enfermedad en población vulnerable esté relacionado con la alta tasa de abandonos que tiene el programa de TB en Colombia, tal como sucede en otras partes del mundo, representando un problema importante de salud pública a nivel mundial (18) .…”
Section: Discussionunclassified
“…Previous studies have revealed that the cost spend towards TB and its treatment is overwhelming, especially for poor people. An average of 20-30% of the annual income and nearly 70% of the per capita income was incurred towards TB treatment [59][60][61][62][63] . The India study highlighted that the average cost towards treatment of TB was much higher than the annual income of patients in the groups with lowest socio-economic status compared to those in groups of higher socio-economic status (68% versus 32% of annual per capita income in the case of Myanmar) 64,65 .…”
Section: Economic Burdenmentioning
confidence: 99%